Relationship of Body Mass Index with Gastroesophageal Reflux Disease Based on Gastroesophageal Reflux Disease Questionnaire Score in the Department of Highways and Construction Development of North Sumatra - Bella Tiara Delfa Pardede; Lidya Imelda Laksmi (Talenta Publisher, 2023)
Background: Gastroesophageal Reflux Disease (GERD) is a pathological condition due to the reflux of stomach contents back into the esophagus that causing symptoms. In Indonesia, there is no clear prevalence of the incidence of GERD. Some risk factors that can cause GERD are age, sex, race, family history, economic status, increased body mass index (BMI) to obesity and smoking. BMI is the most useful and practical indicator for measuring body fat. It is known that an increased BMI can increase the risk for the occurrence of GERD. Objective: Knowing the relationship between BMI and GERD based on the GERD-Q score at the Dinas Bina Marga dan Bina Konstruksi of North Sumatra province. Methods: This research is an analatic study using cross-sectional method. Sampling using simple random sampling. The sample of this study using Gastroesophageal Reflux Disease Questionnaire (GERD-Q) for GERD diagnosis tool and measurement of weight and height to get BMI. Results: The analysis results obtained by Kendalls Tau-b correlation test and found p = 0.773 (p < 0.005). Conclusion: There was no significant relationship between BMI and GERD based on GERD-Q scores on employees of the Dinas Bina Marga dan Bina Konstruksi of North Sumatera.